Muscarinic acetylcholine receptors in the mouse esophagus: focus on intraganglionic laminar endings (IGLEs). Issue 8 (7th June 2013) - Hübsch, M.; Neuhuber, W. L.; Raab, M.
Abstract: Background: IGLEs represent the only low‐threshold vagal mechanosensory terminals in the tunica muscularis of the esophagus. Previously, close relationships of vesicular glutamate transporter 2 (VGLUT2) immunopositive IGLEs and cholinergic varicosities suggestive for direct contacts were described in almost all mouse esophageal myenteric ganglia. Possible cholinergic influence on IGLEs requires specific acetylcholine receptors. In particular, the occurrence and location of neuronal muscarinic acetylcholine receptors (mAChR) in the esophagus were not yet characterized. Methods: This study aimed at specifying relationships of VGLUT2 immunopositive IGLEs and vesicular acetylcholine transporter (VAChT)‐immunopositive varicosities using pre‐embedding electron microscopy and the location of mAChR1‐3 (M1‐3) within esophagus and nodose ganglia using multilabel immunofluorescence and retrograde tracing. Key Results: Electron microscopy confirmed synaptic contacts between cholinergic varicosities and IGLEs. M1‐ and M2‐immunoreactivities (‐iry; ‐iries) were colocalized with VGLUT2‐iry in subpopulations of IGLEs. Retrograde Fast Blue tracing from the esophagus showed nodose ganglion neurons colocalizing tracer and M2‐iry. M1‐3‐iries were detected in about 80% of myenteric ganglia and in about 67% of myenteric neurons. M1‐ and M2‐iry were present in many fibers and varicosities within myenteric ganglia. Presynaptic M2‐iry was detected in all, presynaptic M3‐iry in one‐fifth of motor endplates of striated esophageal muscles. M1‐iry could not be detected in motor endplates of the esophagus, but in sternomastoid muscle. Conclusions & Inferences: Acetylcholine probably released from varicosities of both extrinsic and intrinsic origin may influence a subpopulation of esophageal IGLEs via M2 and M1‐receptors. Abstract : This photomicrograph, from a paper by Hübsch and colleagues ( Neurogastroenterol Motil 2013; 25: e560–73, Figure 5F), shows a section of mouse nodose ganglion that depicts immunoreactivity for the M2 muscarinic receptor in green, and neurons retrogradely labeled from the esophagus with fast blue. Note that the esophagus projecting sensory neuron in the mouse nodose ganglion are M2 receptor‐immunoreactive.